PELATIHAN PENGGUNAAN MICROSOFT OFFICE WORD - M.ansori; Asyari , Hasyim; Muniarti , Wafiah; Saikin (Jurnal Pengabdian Bersama Masyarakat Indonesia, 2025)
Currently, in the era of globalization, the world is becoming increasingly connected and interdependent with one another, rapid developments have occurred in the field of information technology, especially in terms of the use of word processing applications. Teachers at TKIT ASHOPA Praya Central Lombok need adequate skills in using information technology, especially the Microsoft Word application, to improve the quality of human resources. However, the development of Microsoft Office applications that occur every year makes it difficult for teachers to keep up with these developments. Therefore, training activities were carried out which aimed to provide basic knowledge about the Microsoft Word application to TKIT ASHOPA teachers. This training includes an introduction to icons and their functionality, as well as the use of applications in module creation and documentation management. This training lasted for 2 days and was attended by 12 teachers. The ASHOPA TKIT teachers responded enthusiastically to this training, as seen from their active participation in asking questions and discussing the material with the presenters. It is hoped that with this basic training, the understanding of teachers at TKIT ASHOPA Praya Central Lombok can increase.